2022
DOI: 10.1080/19491034.2022.2143106
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility: methods, mechanisms, and biological insights

Abstract: Access to DNA is a prerequisite to the execution of essential cellular processes that include transcription, replication, chromosomal segregation, and DNA repair. How the proteins that regulate these processes function in the context of chromatin and its dynamic architectures is an intensive field of study. Over the past decade, genome-wide assays and new imaging approaches have enabled a greater understanding of how access to the genome is regulated by nucleosomes and associated proteins. Additional mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 395 publications
(567 reference statements)
2
29
0
1
Order By: Relevance
“…5E, F); this may reflect the fact that paternal cross-over events are biased towards the tip of the chromosomes (Broman et al 1998) and, similarly, Subramanian (2019) observed an increase in DSB formation in telomere-proximal regions in yeast. Chromatin accessibility ranked highly in the models of ssDNA and recombination hotspots, consistent with the observation that PRDM9 creates nucleosome-depleted regions (Mansisidor and Risca 2022); however, previous studies have lacked accessibility data from meiotic human cells. Local GC content and meiotic replication timing also ranked highly across models, and both features are known to correlate with levels of recombination (Eyre-Walker 1993; Pratto et al 2021).…”
Section: Resultssupporting
confidence: 78%
“…5E, F); this may reflect the fact that paternal cross-over events are biased towards the tip of the chromosomes (Broman et al 1998) and, similarly, Subramanian (2019) observed an increase in DSB formation in telomere-proximal regions in yeast. Chromatin accessibility ranked highly in the models of ssDNA and recombination hotspots, consistent with the observation that PRDM9 creates nucleosome-depleted regions (Mansisidor and Risca 2022); however, previous studies have lacked accessibility data from meiotic human cells. Local GC content and meiotic replication timing also ranked highly across models, and both features are known to correlate with levels of recombination (Eyre-Walker 1993; Pratto et al 2021).…”
Section: Resultssupporting
confidence: 78%
“…Fig 2A presents an overview on a recent study on true-to-scale DNA-density maps of chromatin where absolute chromatin compaction differences in the range between <5 Mb/μm3 up to >300 Mb/μm3 were described using single molecule localization microscopy (SMLM) 29 . Such massive differences, if confirmed by future studies, have a strong impact on the accessibility of individual macromolecular complexes to their DNA target sites such as the replisome assembly 30 . According to Maeshima and colleagues 31,32 , nucleosome arrangements at a density <40 Mb/µm 3 provide sufficient space to allow a high degree of accessibility for macromolecular protein complexes that have been typically assigned with a size >20nm diameter 32,33 .…”
Section: Introductionmentioning
confidence: 72%
“…High chromatin accessibility for multiple CD5 ZF-Rs can be the consequence of low nucleosome occupancy, or high nucleosome occupancy with low stability and/or an increase in inter-nucleosomal spacing. 4244…”
Section: Discussionmentioning
confidence: 99%